Enhancing physical education performance through blended learning: a study on self-efficacy development. - Yan, Ge; Abdullah, Borhannudin; Abu Saad, Hazizi (Pegem Akademi Yayincilik, 2024)
Background: This study examines the impact of blended learning on self-efficacy development in physical education (PE) courses. The hypothesis is that integrating digital tools and face-to-face interactions enhances student self-efficacy and overall performance in PE settings. Materials and Methods: A quasi-experimental design was employed with a sample of 200 high school students divided into control and experimental groups. The experimental group participated in a blended learning program, which included online instructional videos, interactive simulations, and traditional PE classes. Data on self-efficacy were collected using pre-and post-intervention questionnaires. Results: The results indicated significant improvements in the experimental group's selfefficacy scores, with an average increase of 15% (p < 0.05) compared to the control group, which showed no significant change. Additionally, the experimental group reported a 20% improvement in PE performance tasks. Conclusion: Blended learning approaches in PE can significantly enhance self-efficacy and performance. These findings suggest that digital resources can effectively complement physical training by providing personalized, flexible, and engaging learning experiences.